G107 A Behaviour Assessment Tool for Simulated Neonatal Environment. (7th April 2014) - Ahmed, A; Moore, H; Ranganna, R; Didier, S; Purva, M
Abstract : Aims: The role of behavioural skills in the provision of safe and effective neonatal care is well recognised. 1 Behaviour Assessment Tool (BAT) has been validated for use in simulated neonatal and paediatric environment to assess resuscitation skills. 2 The aim of this study was to develop a modified version of the tool and validate it to assess trainee's performance in stabilising an acutely unwell newborn. Methods: Ethical approval was gained to study the performance of paediatric trainees. The modified Delphi method was used to develop a weighted scoring tool. Video recording of the performance of two trainees was used to train four assessors in use of the tool. Performance of a further sixteen trainees was recorded and was assessed by these assessors. Assessors were blinded to trainee's identity and their years of experience. Results: The scoring tool showed good interrater reliability (ICC = 0.80, CI: 0.58 – 0.92). Mean of the scores achieved by junior trainees was 34.03 (±5.42) compared to senior trainees 38.84 (±1.71). Results of the Independent Samples Mann-Whitney U Test demonstrated a statistically significant difference (P = 0.015) in the distribution of scores achieved by junior and senior trainees. Discussion: The study demonstrates that reliable and valid measurements of behavioural skills can be obtained from simulated neonatal environments using this scoring tool. It is recognised that human factors such as lack of clear leadership, teamwork and communication rather than technical failures represent the greatest threat to complex systems like healthcare. 3 In order to provide robust feedback and training in this area, it is important to have tools to assess behavioural skills in a valid and reliable manner. We feel that our tool can help to assess doctors in training and support the development of a robust training programme for the doctors of the future. References: The Joint Comission. Sentinel event alert. Preventing infant death and injury during delivery. Adv Neonatal Care 2004;4:180–1 Anderson JM, Yaeger KA. The development of a behavioral scoring tool for neonatal resuscitation. In: Society for Medical Simulation Meeting. San Diego, CA . 2006. Reason J. Understanding adverse events: human factors. Qual Health Care 1995;4:80–9